2015
DOI: 10.1111/jar.12175
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use, Offending, and Participation in Alcohol and Drug Treatment Programmes: A Comparison of Prisoners with and without Intellectual Disabilities

Abstract: Substance use may be as common in prisoners with intellectual disabilities as those without this condition. Services may need to reflect on whether their treatment programmes are meeting the needs of all prisoners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Intellectual disability and alcohol use disorders are conditions that individually are associated with poor engagement in care and can go undetected. It is the authors' experience that PWID struggle to access support from addiction services and complete treatment programmes, and this is supported by the literature (Slayter 2010; McGillivray 2016). Interviews with ten PWID found that their main source of support was from community-level intellectual disability services but that although these services are helpful, they could do little to persuade them to change their hazardous drinking patterns (Taggart 2007).…”
Section: Problems With Accessibilitymentioning
confidence: 68%
See 2 more Smart Citations
“…Intellectual disability and alcohol use disorders are conditions that individually are associated with poor engagement in care and can go undetected. It is the authors' experience that PWID struggle to access support from addiction services and complete treatment programmes, and this is supported by the literature (Slayter 2010; McGillivray 2016). Interviews with ten PWID found that their main source of support was from community-level intellectual disability services but that although these services are helpful, they could do little to persuade them to change their hazardous drinking patterns (Taggart 2007).…”
Section: Problems With Accessibilitymentioning
confidence: 68%
“…The true extent of the problem is unclear as there are only limited data regarding the prevalence and severity of alcohol use disorders in PWID (Huxley 2005), and the available data is conflicting: one early study indicated that PWID may be overrepresented in addiction services (Westermeyer 1996), whereas others have found no significant difference in rates of alcohol use disorders compared with those without intellectual disability (VanDerNagel 2011; Bhandari 2015, McGillivray 2016). However, a number of studies (Robertson 2000; Asscher 2012), including a large, comprehensive population-based UK study (Cooper 2007), suggest that prevalence is low compared to the general population.…”
Section: Prevalence Of Alcohol Use Disorders In Pwidmentioning
confidence: 99%
See 1 more Smart Citation
“…In a psychiatric outpatient facility (n = 115), 17% alcohol misuse, 6% cannabis misuse and 3% cocaine misuse was found (Chaplin et al 2011). In offenders with ID, several studies found SUD rates of approximately 60% (Crocker et al 2007;Hassiotis et al 2011;Mcgillivray et al 2015). On the other hand, in several community based samples only 1% had a SUD diagnosis (Cooper et al 2007;Taggart et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…Several demographic, contextual and diagnostic factors have been associated with SU(D) in MBID, such as younger than 30 years old, male, no structured daytime activities VanDerNagel et al 2011a), and living independently (Taggart et al 2006;To et al 2014). Furthermore, SU(D) in MBID is associated with psychiatric or behavioral (Chaplin et al 2011;Didden et al 2009) and forensic problems (Crocker et al 2007;Hassiotis et al 2011;Mcgillivray et al 2015). For instance, among 39 patients with MBID in an inpatient treatment facility, 28% abused alcohol, and 36% drugs (Didden et al 2009).…”
Section: Introductionmentioning
confidence: 99%